Character Education for Children in Indonesia - Ni Luh Putu Rastiti Era Agustini (English Education Department STKIP Agama Hindu Singaraja, 2021)
Character education is one of the aspects in education which is important for students before they face the real world society. Character education can be learned in the formal education with the support of environment such as school staffs, teachers, and also parents. Moreover, character education can also help students to deal with academic field. Character education is not directly taught in school as a subject but it includes in the subjects learn by students such as science, social science, language and many more. Even though character education has been taught at school, there is still something unwanted happens to students especially children. This thing can be prevented using the character education. This study focuses in describing the character education especially for children in Indonesia.